ANALISA PERSEPSI KARYAWAN TENTANG PENGARUH INTELLECTUAL CAPITAL TERHADAP CUSTOMER SATISFACTION DAN FINANCIAL PERFORMANCE (STUDI KASUS PADA SEKTOR PERHOTELAN DAN RESTAURANT DI SURABAYA) - Vania Sabella (Business Accounting Review, 2016)
This study aimed to know the direct positive effect of intellectual capital to customer’s satisfaction, customer’s satisfaction to financial performance, and intellectual capital to the financial performance based on the perceptions of employees in the hotel and restaurant sectors in Surabaya. The data obtained were processed by using smart software-PLS. The results showed a positive relationship of intellectual capital to customer’s satisfaction, customer’s satisfaction to financial performance, and intellectual capital to the financial performance based on the perceptions of employees in the hotel and restaurant sectors in Surabaya. Customer’s satisfaction was able to be intervening variable between intellectual capital with financial performance because of the direct relationship between intellectual capital and financial performance through greater customer’s satisfaction than if not through customer’s satisfaction.